Issues of psychological anthropology - Golovko, B. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
Anthropology is understood as the holistic science of man. Anthropology describes a discipline comprising the study of primate and human evolution, prehistoric archeology, linguistics and social/cultural anthropology. This definition raises the following questions: what is this disparate collection of disciplines doing under one heading, itself claiming to be a discipline? And another question is "What is not the "science of man"? Since it grew up around museums in large part, "artifacts" loomed large, and for long stretches of the discipline’s history ethnographers "collected" customs and culture traits much as their museological colleagues "collected" artifacts. As anthropology eventually developed in many universities independently of museums, artifacts declined in importance. As a discipline, anthropology started to consider in the 1860s, and sturted to be teached in the universities by the turn of the century. Anthropology developed originally outside the universities: Tylor in England was a Quaker businessman, Morgan in the USA was a lawyer. Tylor’s work "Anthropology", which was published in 1881, marks the establishment of anthropology as a discipline in England. Morgan’s work "Ancient society", which was published in 1877 did the same in England. The last of the classics of anthropology B. Malinowski for the first time combined the anthropological community through clear descriptions and clear system of ordering material of anthropological research, which started to be called "functionalism". Strong supporter of democracy B. Malinowski spoke sharply about the anthropological basis of socio-cultural traditions. A wide range of anthropological problems of psychological anthropology affected a number of relevant thereto disciplines such as archeology, social and cultural anthropology, legal anthropology, historical anthropology, anthropological linguistics, ecological anthropology, economic anthropology, business anthropology, visual anthropology, pedagogical anthropology, religious anthropology, ethnology, ethnosociology, ethnography, and others. The emergence of the classical school "Culture and personality" we owe to R. Benedict. By this time there is the first period of crisis of theoretical psychological anthropology. Well-known founder of structural anthropology C. Levi-Strauss in the tenth chapter "The effectiveness of character" analyzes real shamanic practices of Kuna tribe. In parallel to symbolic anthropology developed cognitive anthropology. These works and textbooks issued based on them give hope to overcome methodological crisis and achieve sustainable development of psychological anthropology in the ХХІ century.